2013
DOI: 10.1118/1.4795347
|View full text |Cite
|
Sign up to set email alerts
|

MR safety assessment of potential RF heating from cranial fixation plates at 7 T

Abstract: The findings suggested no evidence for noteworthy RF-related heating in humans after craniotomy using the described implants and for the particular RF coil that was used in this study. Here, identical transmit power restrictions apply with or without the implants. For other RF coils, the maximum permissible input power should be reduced by 10% until further simulations may indicate otherwise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…Our experimental results showed that MRI-related heating does not pose a major health risk to subjects with any of the four commonly used extracranial neurosurgical implants tested under the conditions used in this study. This is in agreement with preliminary simulation results from another group [17]. MRI-related heating is predominantly associated with the RF fields near an implant (although gradient fields may also contribute modestly to MRI-related heating, this was outside the scope of the present study).…”
Section: Discussionsupporting
confidence: 91%
“…Our experimental results showed that MRI-related heating does not pose a major health risk to subjects with any of the four commonly used extracranial neurosurgical implants tested under the conditions used in this study. This is in agreement with preliminary simulation results from another group [17]. MRI-related heating is predominantly associated with the RF fields near an implant (although gradient fields may also contribute modestly to MRI-related heating, this was outside the scope of the present study).…”
Section: Discussionsupporting
confidence: 91%
“…An important limitation of all current ultra-highfield MRI studies is due to exclusion of scans in patients with most metallic implants. Despite high clinical interest for follow-up, patients after endovascular coiling or surgical clipping cannot be enrolled in 7-T MRI studies at present, as previous aneurysm treatment is still a contraindication for MRI scans >3 T. The first promising investigations on implant safety at 7 T have already been performed [39], but before patients with for example multiple UIAs (e.g. one clipped, one coiled, two conservatively observed due to very small size) can be followed up, further studies on implant safety are mandatory.…”
Section: Discussionmentioning
confidence: 97%
“…Besides these studies, other published articles describe safety studies of aneurysm clips [59], implants for earnose-throat surgery [60], upper eye implants [61], cranial fixation plates [62], an EEG-cap [63], intraocular lenses [64], actuators [65], ballistic objects [66], and extracranial neurosurgical implants [67].…”
Section: Safety Of Implantsmentioning
confidence: 99%